Autophagy in hemorrhagic stroke: Mechanisms and clinical implications. (April 2018) - Li, Haiying; Wu, Jiang; Shen, Haitao; Yao, Xiyang; Liu, Chenglin; Pianta, S.; Han, J.; Borlongan, C.V.; Chen, Gang
Highlights: There is a dual role of autophagy in brain cells after stroke. The role of autophagy has cell specificity in brain after stroke. There is a crosstalk between apoptosis, necrosis and autophagy after stroke. The integrity of autophagic flux is associated with divergent outcomes of stroke. Autophagy may participates in inflammation regulation after stroke. Abstract: Accumulating evidence advances the critical role of autophagy in brain pathology after stroke. Investigations employing autophagy induction or inhibition using pharmacological tools or autophagy-related gene knockout mice have recently revealed the biological significance of intact and functional autophagy in stroke. Most of the reported cases attest to a pro-survival role for autophagy in stroke, by facilitating removal of damaged proteins and organelles, which can be recycled for energy generation and cellular defenses. However, these observations are difficult to reconcile with equally compelling evidence demonstrating stroke-induced upregulation of brain cell death index that parallels enhanced autophagy. This begs the question of whether drug-induced autophagy during stroke culminates in improved or worsened pathological outcomes. A corollary fascinating hypothesis, but presents as a tricky conundrum, involves the effects of autophagy on cell death and inflammation, which are two main culprits in the disease progression of stroke-induced brain injury. Evidence has extended the roles of autophagy in inflammation via cytokine regulation in an unconventional secretion manner or by targeting inflammasomes for degradation. Moreover, in the recently concluded Vancouver Autophagy Symposium (VAS) held in 2014, the potential of selective autophagy for clinical treatment has been recognized. The role of autophagy in ischemic stroke has been reviewed previously in detail. Here, we evaluate the strength of laboratory and clinical evidence by providing a comprehensive summary of the literature on autophagy, and thereafter we offer our perspectives on exploiting autophagy as a drug target for cerebral ischemia, especially in hemorrhagic stroke.